Bibliometric examination of "Bona Vacantia": charting patterns and research trends - Abdullah Sanek, Siti Khadijah; Halim, Akmal Hidayah (AMH International, 2024)
This paper employs a bibliometric analysis to examine the primary sources of publication, authorship, citations, and research trends concerning Bona vacantia. Bona vacantia, often known as ownerless property, carries significant legal and economic significance on a global scale. Comprehending the academic discussion surrounding a topic benefits legal professionals, policymakers, and researchers. Retrieving 645 relevant articles from the Scopus database spanning 2003 to 2023, the study employs data refining and various bibliometric methods, including cluster and network analysis and word cloud generation. The analysis reveals 158 contributors from 69 countries, predominantly publishing articles. It identifies key articles, authors, and journals shaping the discourse on Bona vacantia. Although the insights provided are valuable, it is crucial to understand the limits in terms of database coverage, chronology, and paper scope. Future research should incorporate diverse databases and extend temporal perspectives to understand Bona vacantia comprehensively. This study recommends a broader research expansion to enhance understanding of this multifaceted subject.